Perioperative management and outcome of fracture treatment in patients with haemophilia without inhibitors. (9th October 2015) - Strauss, A. C.; Pennekamp, P. H.; Placzek, R.; Schmolders, J.; Friedrich, M. J.; Oldenburg, J.; Burger, C.; Müller, M. C.
Abstract : Introduction: Fractures in persons with haemophilia (PWH) are not uncommon and require an interdisciplinary approach to maintain haemostasis during surgical treatment. Aim: The aim of this study was to evaluate the perioperative management and outcome in PWH following fracture fixation compared to a matched non‐haemophilic control group. Methods: A cohort of 44 PWH who underwent 46 surgical fracture fixations was retrospectively compared to 46 non‐haemophilic patients (matched‐pair controls). Patients were classified according to the fracture localization: (i) proximal upper extremity (PrUEx; n = 7), (ii) distal upper extremity (DiUEx; n = 12), (iii) proximal lower extremity (PrLEx; n = 13) and (iv) distal lower extremity (DiLEx; n = 14). Both groups were assessed for length of hospital stay, duration of surgery, drainage use and complication rates. Results: There was no significant difference regarding the duration of the preoperative hospital stay between PWH and controls. Only PWH who were operated at the DiUEx stayed significantly longer in hospital (4.8 ± 3.7 days) than controls (2.2 ± 2.3 days; P = 0.039). Operation time was significantly longer in PWH with fractures treated at the DiLEx (64.9 ± 26.6 min) compared to the controls (49.8 ± 37.9 min; P = 0.035). Neither frequency nor duration of surgical drainage placement differed significantly between the two groups. The overall complication rate in both groups was low without a statistically significant difference. Conclusion: An optimal interdisciplinary perioperative management provided the surgical treatment of fractures in PWH can be performed safely with a low complication rate.